2016
DOI: 10.1017/s000711451500522x
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide burden of gastric cancer in 2012 that could have been prevented by increasing fruit and vegetable intake and predictions for 2025

Abstract: The regional and temporal variation in patterns of fruit and vegetable intake contributes to differences in the impact on gastric cancer burden across regions and over the years. We aimed to estimate the proportion and absolute number of gastric cancer cases that could have been prevented in 2012 with an increase in fruit and vegetable intake up to the levels defined by the Global Burden of Disease as the theoretical minimum-risk exposure distribution (300 and 400 g/d, respectively), as well as the correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The associations for those receiving high school and college/university education were insignificant in overall patients and most subgroups, which could be partly explained by the small case numbers in these groups. People having majorly vegetables for food had significantly less frequent GaC, which is also supported by previous studies [20,21]. Furthermore, we found that more frequent vegetable/fruit intake was significantly associated with a reduced frequency of cardia cancer but not of non-cardia cancer.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The associations for those receiving high school and college/university education were insignificant in overall patients and most subgroups, which could be partly explained by the small case numbers in these groups. People having majorly vegetables for food had significantly less frequent GaC, which is also supported by previous studies [20,21]. Furthermore, we found that more frequent vegetable/fruit intake was significantly associated with a reduced frequency of cardia cancer but not of non-cardia cancer.…”
Section: Discussionsupporting
confidence: 91%
“…The FS for passive smoking was also significantly associated with GaC (OR=1. 21). No significant associations of GaC with marital status, or histories of hepatitis, diabetes, hypertension, or allergy were observed.…”
Section: Basic Modelsmentioning
confidence: 89%
“…The worldwide consumption of fruits and vegetables is low, particularly in low and middle-income countries 61 and, when assuming a causal relationship between fruits and vegetables intake and the occurrence of gastric cancer, an increase in the overall consumption to at least 300 g of fruits/day and 400 g vegetables/day, was estimated to prevent 6.0% to 11.5% of gastric cancer cases in these settings, by 2025. 62 The main limitation of the current study is the case-control design of the included studies, which may have potentially yielded inaccurate measures of fruit and vegetable consumption. As past dietary habits were reported by participants, recall bias may have occurred, particularly among patients, as changes in lifestyle may occur as cancer develops and becomes symptomatic.…”
Section: Resultsmentioning
confidence: 95%
“…Both cases and controls reported low levels of fruits and vegetables intake, with the median of consumption not reaching the amount recommended of five portions a day (at least two of fruits and three of vegetables) 44 in most studies. The worldwide consumption of fruits and vegetables is low, particularly in low and middle‐income countries 61 and, when assuming a causal relationship between fruits and vegetables intake and the occurrence of gastric cancer, an increase in the overall consumption to at least 300 g of fruits/day and 400 g vegetables/day, was estimated to prevent 6.0% to 11.5% of gastric cancer cases in these settings, by 2025 62 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, notably the Mediterranean diet is often viewed as a set of practices and a life-style much more so than a mere diet or dietary scheme. Interestingly, a study showed that if fruit and vegetable intake levels increased to 300 and 400 g/day respectively, that could lead to a significant reduction in gastric cancers, particularly in the developing countries [92]. …”
Section: The Role Of Dietary Berries In Various Types Of Cancermentioning
confidence: 99%